Production and partial purification of lipase produced by Burkholderia cenocepacia ST8 using used engine oil as substrate - Lau, Hui Lane (2020)
Pollution of environment from the impacts of improper disposal of used engine oil (UEO) that lead to the endangering of biota had become a global environmental issue nowadays. UEO contains aliphatic and aromatic hydrocarbon mixtures. The bioconversion of UEO into useful and cost-effective product (i.e., lipase) via microbial fermentation, can reduce the risk of releasing UEO into the environment seems to be very attractive strategy. The aim of this study was to investigate the production, optimization, and partial purification of extracellular lipase by an indigenous Burkholderia cenocepacia ST8 in submerged fermentation using shake flask. The effect of lipid and the components of UEO employed for enhancement of lipase production were investigated. Statisticalbased approaches were employed to optimize the fermentation medium based on UEO for the improvement of lipase production by B. cenocepacia. The crude lipase from B. cenocepacia was also partially purified by solvent/salt-based aqueous two-phase systems (ATPS) using UEO-based fermentation broth as feedstock. Preliminary results showed that lipase production by B. cenocepacia using UEO was induced in the presence of Tween 80 in the culture. The role of UEO fractions (hydrocarbon content) in the presence of Tween 80 in relation to the enhancement of lipase production was also studied. On individual hydrocarbon system, aliphatic hydrocarbon was found to be more favorable as compared to aromatic hydrocarbon in the enhancement of lipase production. The use of the mixtures of aliphatic (C15 or C16) and aromatic hydrocarbon gave substantial increment in growth of B. cenocepacia and lipase production as compared to basal medium (BM). Lipase production could be improved by the addition of C40 or benzene, in BM containing UEO. Response surface methodology (RSM) predicted the optimized media constituents to be 2.28% Tween 80 (v/v), 2.26% UEO (v/v), 0.79% nutrient broth (w/v) and 1.33% gum arabic (w/v), with actual observed lipase activity of 216 U/mL. The RSM-optimized system as well as ANN-GA optimized system revealed approximately 1.6-fold increment in lipase production as compared to non-optimized medium. Nutrient broth and Tween 80 were found to be the most important variables that greatly influenced the lipase activity. Partial purification of lipase was obtained with a purification-fold of 4.8 and RT of 141% in a 1-propanol/sodium citrate ATPS system. Enhancement of lipase production is associated with the types of hydrocarbons, individual and in combination as well as the presence of surfactant. The combined effects of aliphatic and aromatic hydrocarbons (UEO content) in the presence of Tween 80 can enhance lipase production. RSM and ANN-GA approaches are effective tools for predicting and optimizing fermentation medium for lipase production. Solvent/salt-based ATPS considered as economically feasible and potential downstream method to purify lipase with high enzyme recovery from UEObased fermentation broth as feedstock.